Blood α-tocopherol, γ-tocopherol levels and risk of prostate cancer: a meta-analysis of prospective studies. - Ran Cui; Zhu-Qing Liu; Qing Xu (PLoS ONE, 2014)
BACKGROUND: Epidemiological studies that have examined the association of blood α-tocopherol and γ-tocopherol (the principal bioactive form of vitamin E) levels with the risk of prostate cancer have yielded inconsistent results. In addition, a quantitative assessment of published studies is not available. METHODS AND FINDINGS: In this meta-analysis, relevant studies were sought by a search of the PubMed and Embase databases for articles published up to October 2013, with no restrictions. Bibliographies from retrieved articles also were scoured to find further eligible studies. Prospective studies that reported adjusted relative risk (RR) estimates with 95% confidence intervals (CIs) for the association between blood tocopherol levels and the risk of prostate cancer were included. Nine nested case-control studies involving approximately 370,000 participants from several countries were eligible. The pooled RRs of prostate cancer for the highest versus lowest category of blood α-tocopherol levels were 0.79 (95% CI: 0.68-0.91), and those for γ-tocopherol levels were 0.89 (95% CI: 0.71-1.12), respectively. Significant heterogeneity was present among the studies in terms of blood γ-tocopherol levels (p = 0.008) but not in terms of blood α-tocopherol levels (p = 0.33). The risk of prostate cancer decreased by 21% for every 25-mg/L increase in blood α-tocopherol levels (RR: 0.79; 95% CI: 0.69-0.91). CONCLUSIONS: Blood α-tocopherol levels, but not γ-tocopherol levels, were inversely associated with the risk of prostate cancer in this meta-analysis.